Adding semantics to internet of things. (14th January 2014) - Su, Xiang; Riekki, Jukka; Nurminen, Jukka K.; Nieminen, Johanna; Koskimies, Markus; Mustafee, Navonil; Bessis, Nik; Barolli, Leonard; Chen, Xiaofeng; Xhafa, Fatos
Summary The development of Internet of Things (IoT) applications can be facilitated by encoding the meaning of the data in the messages sent by IoT nodes, but the constrained resources of these nodes challenge the common Semantic Web solutions for doing this. In this article, we examine enabling technologies for adding semantics to the IoT. Especially, we analyze data formats, which enable IoT applications consume semantic IoT data in a straightforward and general fashion, and evaluate resource usage of different alternatives with a sensor system. Our experiment illustrates encoding and decoding of different data formats and shows how big a difference a data format can make in energy consumption. Copyright © 2014 John Wiley & Sons, Ltd.